2019
DOI: 10.3390/met9030364
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Energy Consumption and CO2 Emission for Three Steel Production Routes—Integrated Steel Plant Equipped with Blast Furnace, Oxygen Blast Furnace or COREX

Abstract: High CO2 emissions and energy consumption have greatly restricted the development of China’s iron and steel industry. Two alternative ironmaking processes, top gas recycling-oxygen blast furnace (TGR-OBF) and COREX®, can reduce CO2 emissions and coking coal consumption in the steel industry when compared with a conventional blast furnace (BF). To obtain parameters on the material flow of these processes, two static process models for TGR-OBF and COREX were established. Combining the operating data from the Jin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 24 publications
(36 reference statements)
0
24
0
Order By: Relevance
“…In simulating the CCB reaction behavior under each scenario, the environment variables were determined by the experimental conditions. Owing to the sintering of the iron-oxide particles, it was difficult to determine a gs in the reaction rates of reactions (1)(2)(3). A trial-and-error method was used, and it was found that an effective a gs of 1500 m 2 •m −3 was adequate.…”
Section: Ccb Model Validation Under Simulated Bf Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In simulating the CCB reaction behavior under each scenario, the environment variables were determined by the experimental conditions. Owing to the sintering of the iron-oxide particles, it was difficult to determine a gs in the reaction rates of reactions (1)(2)(3). A trial-and-error method was used, and it was found that an effective a gs of 1500 m 2 •m −3 was adequate.…”
Section: Ccb Model Validation Under Simulated Bf Conditionsmentioning
confidence: 99%
“…Although these processes are well-established and highly efficient, they face challenges related to lowering energy consumption and minimizing CO 2 emissions that are needed to create a more efficient and sustainable iron and steel industry. As the BF sector accounts for 75%-80% of the total energy consumption and it generates the largest amount of CO 2 emissions [2,3] finding ways for the BF industry to conform to these environmentally standards is crucial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of lump ore or pellets also dispenses with the need of sinter plants. Since coking and sintering plants are not required for the COREX process, substantial cost savings of up to 20% can be achieved in the production of hot metal, of a grade similar to that of the blast furnace [3]. Since the distribution of charged burden plays a crucial role in determining the gas flow and thus in achieving a stable operation in BF and SF, it is of considerable importance to investigate the burden distribution influenced by the complicated charging system of COREX MG.…”
Section: Introductionmentioning
confidence: 99%
“…The use of lump ore or pellets also dispenses with the need of sinter plants. Since coking and sintering plants are not required for the COREX process, substantial cost savings of up to 20% can be achieved in the production of hot metal, of a grade similar to that of the blast furnace [3].…”
Section: Introductionmentioning
confidence: 99%